Crystallographic and Computational Study of Purine: Caffeine Derivative. (30th March 2014) - Mabied, Ahmed F.; Shalaby, Elsayed M.; Zayed, Hamdia A.; Farag, Ibrahim S. A.
Abstract : The crystal structure of substituted purine derivative, 8-(3-butyl-4-phenyl-2, 3-dihydrothiazol-2-ylidene)hydrazino-3, 7-dihydro-1, 3, 7-trimethyl-1H-purine-2, 6-diones, caffeine derivative, has been determined. It crystallized in monoclinic system and space group P21 /c with unit cell parameters a = 15.2634 (9), b = 13.4692 (9), c = 11.9761 (7) Å, and β = 108.825 (3)°. Although each constituting moiety of the structure individually is planar, nonplanar configuration for the whole molecule was noticed. Molecular mechanics computations indicated the same nonplanar feature of the whole molecule. A network of intermolecular hydrogen bonds contacts and π interactions stabilized the structure.